Law No. 166 of the year 2022 On Determining an exceptional cost-of-living allowance for the Workers Addressed by the Provisions of the Civil Service Law, the State Civil Servants Non-Addressed thereby, and on Determining an Exceptional Grant for the Workers of the Public Sector Companies and Public Business Sector Companies And Giving an exceptional Grant To pensioners or their beneficiaries = قانون رقم 166 لسنة 2022 بتقرير علاوة غلاء معيشة استثنائية للموظفين المخاطبين بقانون الخدمة المدنية والعاملين بالدولة غير المخاطبين به وبتقرير منحة استثنائية للعاملين بشركات القطاع العام وقطاع الأعمال العام ومنح أصحاب المعاشات أو المستحقين عنهم منحة استثنائية - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic